Nanostructured materials for advanced technological applications - Reithmaier, Johann Peter (NATO science for peace and security series. Physics and biophysics)
This book is based on the lectures and contributions of the NATO Advanced Study Institute on "Nanostructured Materials for Advanced Technological Applications" held in Sozopol, Bulgaria, 1-13 June, 2008. It gives a broad overview on this topic, as it combines basic theoretical articles, papers dealing with experimental techniques, and contributions on advanced and up-to-date applications in fields such as electrochemistry, optoelectronics, data storage, sensor technique, and biotechnology. In addition, it presents an interdisciplinary approach as the authors came from different fields such as physics, chemistry, engineering, materials science and biology. Some emphasize is given to the fields of nanostructured/nanoscaled thin films and nanocomposites, again stretching from basic theoretical over experimental (including both, fabrication and characterization) to application oriented topics. A major advantage of the book, which represents the knowledge of experts from 19 countries, is the combination of longer papers introducing the basic knowledge on a certain topic, and brief contributions highlighting special methods and applications.